The Effect of Financial Literacy and Lifestyle on Financial Management of XI Grade Students at SMK Negeri 1 Surakarta - Salsa Septy Mutiarasari; Titik Ulfatun (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research endeavors to examine the effect of financial literacy and lifestyle on the financial management of eleventh-grade students at SMK Negeri 1 Surakarta, both individually and collectively. The research employs a quantitative method, with a population of 357 grade XI students at SMK Negeri 1 Surakarta and a sample size of 186 students. Probability sampling, specifically the proportionate stratified random sampling method based on the Krejcie and Morgan table, was utilized for sample selection. Primary data for the study were gathered through the administration of questionnaires, and data analysis was conducted using multiple linear regression analysis. The findings indicate that (1) financial literacy has a partial influence on the financial management of grade XI students at SMK Negeri 1 Surakarta, (2) lifestyle also has a partial impact on the financial management of these students, and (3) the combined effects of financial literacy and lifestyle significantly influence the financial management of grade XI students at SMK Negeri 1 Surakarta.